Subcutaneous fat necrosis of the newborn, cerebral infarct and severe hypereosinophilia. - Proença, E.; Alegria, A.; Rosário, C.; Barbot, J. (European Journal of Pediatric Dermatology, 2004)
Subcutaneous fat necrosis of the newborn (SCFN) is a transient uncommon cutaneous disease occurring during the first days or weeks after birth, which affects newborns that have experienced perinatal distress associated with tissue hypoxia. We report a patient with an extensive form of SCFN complicated with hypercalcemia, who later developed a middle cerebral artery thrombosis and a drug related striking hypereosinophilia. This association, never previously described, seems to be occasional.